Analysis of spatial inequalities based on social, economic, and physical indicators (case example of Urmia metropolis) - shahrivar rostaei; Akbar Asgharizamani; shiva Alizadeh (جغرافیای اجتماعی شهری, 2023)
Introduction: This area of the city is critical because its structure is an indispensable system, consisting of several units, and of all the various elements, which make their inconsistency an impression on the whole system and the whole of a city's structure. The survey of inequality and its funds is located in different geographical borders in recent years of the work of Harriet and politicians. The existence of inequality and various dimensions has not been judged by the topography of an important development. The aim of this inquiry into alien inequality or other interpretation of the distribution of space is to maintain an economic, social, and domestic involvement.Data and Method: The research method is descriptive-analytical and practical in terms of purpose. After theoretical investigations of population and housing census data for three consecutive periods (1385, 1390, 1395) and converting them into per capita and different ratios into indexes, to investigate the inequality situation, Also, the recognition of the spatial pattern of the expansion of inequality for the three extracted periods of the research implementation process based on these indicators and spatial statistics models, Spatial Statistics tools, Hot Spot Analysis and Moran's I spatial autocorrelation have been used in Arc/GIS software.Results: According to the numerical output, Moran's index is equal to 0.071892, 0.144981, 0.633505 for the years 1385, 1390, 1395, respectively, and since its value is positive and tends to one, and according to If the p-value is zero and the calculated Z value (its absolute value) is large, then it is within the confidence limit, and as a result, the data have spatial autocorrelation. Therefore, the distribution pattern of inequality is a cluster.Conclusion: In general, the result shows that the situation arises from a class distance, a duality in the city, and that the difference between the sexes in the time of the observation, and that it is necessary to keep a town management for themselves, at least of the necessary.